Performance and Variability Trade-offs of CMOS PTAT Generator Topologies for Voltage Reference Applications - de Lima, Vanessa; Ataide, Rodrigo; Bampi, Sergio; Klimach, Hamilton (Symposium on Integrated Circuits and Systems Design (SBCCI), 2020)
This work presents the analysis, design, and performance evaluation of three usual CMOS proportional to absolute temperature (PTAT) voltage generators, with emphasis on variability effects. Minimization or compensation of the main error sources, such as fabrication variability and intrinsic non-linearities, is an important design challenge required to increase the precision and robustness of a voltage reference. The CMOS PTAT topologies are analytically described and design methodologies for PTAT circuits in subthreshold are presented. The compromises between design conditions and resulting performance are evaluated through simulation for these three PTAT generators, including linearity with temperature, temperature coefficient (TC), and variability impact. Monte-Carlo simulations demonstrated the sensitivity of each topology to fabrication variability, showing that the self-cascode MOSFET structure presents the best accuracy of TC, nominal PTAT voltage, and linearity with temperature.